ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, TIPE INDUSTRI, DAN PENGUNGKAPAN MEDIA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014) - Rheza Dwi Respati; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of proftitability, leverage, firm size,industry classification and media exposure to Corporate Social Resposibility disclosure. The dependent variable is Corporate Social Resposibility disclosure. Independent variable are protfitability, leverage, firm size, industry classification and media exposure. This study was used secondary data from annual reports of manufacturing companies which were listed on Indonesia Stock Exchange in 2014. Samples were 111 manufacturing companies. This study used purposive sampling method and multiple linear regression as the analysis method. Before being conducted by regression test, it was examined by using the classical assumption tests. The results of this study indicate that profitability and leveragedid not have significant influence to the CSR disclosure meanwhile the firm size,industry classification and media exposure have a positive significant influence to CSR disclosure.